A tissue‐engineered human dermal construct utilizing fibroblasts and transforming growth factor β1 to promote elastogenesis. Issue 3 (4th March 2013) - Sommer, Nadine; Sattler, Martin; Weise, Julia M.; Wenck, Horst; Gallinat, Stefan; Fischer, Frank
Abstract Numerous studies have shown that extracellular matrix (ECM)‐based scaffolds are suitable for dermal constructs for the differentiation of various cell types in vitro and for constructive tissue remodeling after implantation in vivo. However, a shortcoming of these ECM materials is its limited elastogenesis. Elastic fibers constitute an essential component of mammalian connective tissue and the presence of elastic fibers is crucial for the proper function of the cardiovascular, pulmonary, and intestinal systems. Since it is still largely unknown how cells coordinate the molecular events of elastic‐fiber assembly, understanding the ability to regenerate elastic fibers in tissues remains a significant challenge. For this reason, human neonatal dermal fibroblasts (HDFneo) were analyzed for their potential to serve as a cell culture model for elastic fiber assembly. Using optical technologies such as multiphoton laser‐scanning microscopy (MPSLM) we demonstrate that HDFneo stimulated with transforming growth factor β1 (TGF‐β1) are able to produce a distinct and complex elastic fiber system in vitro. As shown by the desmosine and isodesmosine content, crosslinked elastic fibers were formed within the 3D ECM‐based scaffold. This tissue‐engineered dermal construct may prove to be an effective template for the development of medicinal approaches in regenerative soft skin tissue reconstruction through TGF‐β1 induction.